2018
DOI: 10.1186/s12964-018-0284-4
|View full text |Cite
|
Sign up to set email alerts
|

Macrophage migration inhibitory factor contributes to the pathogenesis of benign lymphoepithelial lesion of the lacrimal gland

Abstract: BackgroundBenign Lymphoepithelial Lesion (BLEL) is a rare disease observed in the adult population. Despite the growing numbers of people suffering from BLEL, the etiology and mechanisms underlying its pathogenesis remain unknown.MethodsIn the present study, we used gene and cytokines expression profiling, western blot and immunohistochemistry to get further insight into the cellular and molecular mechanisms involved in the pathogenesis of BLEL of the lacrimal gland.ResultsThe results showed that Macrophage Mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 93 publications
0
6
0
Order By: Relevance
“…Skin tissue at the wound site was harvested and fixed with formalin and embedded in paraffin blocks, and then 4 μm thick paraffin sections were mounted on glass slides for histological staining. IHC and IF of the paraffin-embedded tissue sections were performed as previously indicated [ 51 ]. Briefly, sections were dewaxed and rehydrated by subsequent immersion in xylene, ethanol (100%, 95%, 70%, and 50%) and deionized H 2 O. Antigen was then retrieved in citrate buffer, and non-specific staining between the primary antibodies (Table S1 A) and the tissue was blocked by incubation in 1% goat serum in PBS for 60 min at RT.…”
Section: Methodsmentioning
confidence: 99%
“…Skin tissue at the wound site was harvested and fixed with formalin and embedded in paraffin blocks, and then 4 μm thick paraffin sections were mounted on glass slides for histological staining. IHC and IF of the paraffin-embedded tissue sections were performed as previously indicated [ 51 ]. Briefly, sections were dewaxed and rehydrated by subsequent immersion in xylene, ethanol (100%, 95%, 70%, and 50%) and deionized H 2 O. Antigen was then retrieved in citrate buffer, and non-specific staining between the primary antibodies (Table S1 A) and the tissue was blocked by incubation in 1% goat serum in PBS for 60 min at RT.…”
Section: Methodsmentioning
confidence: 99%
“…Skin tissue at the wound site was harvested and xed with formalin and embedded in para n blocks, and then 4 μm thick para n sections were mounted on glass slides for histological staining. IHC and IF of the para n-embedded tissue sections were performed as previously indicated 93 . Brie y, sections were dewaxed and rehydrated by subsequent immersion in xylene, ethanol (100%, 95%, 70%, and 50%) and deionized H 2 O. Antigen was then retrieved in citrate buffer, and non-speci c staining between the primary antibodies (Table S1A) and the tissue was blocked by incubation in 1% goat serum in PBS for 60 minutes at RT.…”
Section: In Vitro Tube Formation Assaymentioning
confidence: 99%
“…Benign lymphoepithelial lesion, also known as Mikulicz disease, occurs in the parotid gland, lacrimal gland, and other sites and is characterized by lymphocyte infiltration associated with epithelial hyperplasia [ 1 , 2 ]. Lacrimal-gland benign lymphoepithelial lesion (LGBLEL) is an immune-related inflammatory lesion that is most common in middle-aged women [ 3 , 4 ]. The main manifestations are diffuse enlargement of the bilateral or unilateral lacrimal glands and eyelid swelling.…”
Section: Introductionmentioning
confidence: 99%
“…The main manifestations are diffuse enlargement of the bilateral or unilateral lacrimal glands and eyelid swelling. Typical pathological manifestations are diffuse infiltration of lymphocytes and plasma cells in the lacrimal tissue, atrophy and disappearance of glands, and hyperplasia of the fibrous tissue [ 3 , 4 ]. Studies have shown elevated immunoglobulin 4 (IgG4) expression levels in some LGBLEL serum and tissues; therefore, LGBLEL with positive IgG4 expression is considered IgG4-related ophthalmic disease (IgG4-ROD) [ 5 ].…”
Section: Introductionmentioning
confidence: 99%